Differential Expression of Candidate Salivary Effector Genes in Pea Aphid Biotypes With Distinct Host Plant Specificity - Boulain, Hélène; Legeai, Fabrice; Jaquiéry, Julie; Guy, Endrick; Morlière, Stéphanie; Simon, Jean-Christophe; Sugio, Akiko (Frontiers in Plant Science, 2019)
Effector proteins play crucial roles in determining the outcome of various plant–parasite interactions. Aphids inject salivary effector proteins into plants to facilitate phloem feeding, but some proteins might trigger defence responses in certain plants. The pea aphid, Acyrthosiphon pisum, forms multiple biotypes, and each biotype is specialized to feed on a small number of closely-related legume species. Interestingly, all the previously-identified biotypes can feed on Vicia faba; hence, it serves as a universal host plant of A. pisum. We hypothesized that the salivary effector proteins have a key role in determining the compatibility between specific host species and A. pisum biotypes and that each biotype produces saliva containing a specific mixture of effector proteins due to differential expression of encoding genes. As the first step to address these hypotheses, we conducted two sets of RNA-seq experiments. RNA-seq analysis of dissected salivary glands from reference alfalfa- and pea-specialized A. pisum lines revealed common and line-specific repertoires of candidate salivary effector genes. Based on the results, we created an extended catalogue of A. pisum salivary effector candidates. Next, we used aphid head samples, which contain salivary glands, to examine biotype-specific expression patterns of candidate salivary genes. RNA-seq analysis of head samples of alfalfa- and pea-specialized biotypes, each represented by three genetically distinct aphid lines reared on either a universal or specific host plant, showed that a majority of the candidate salivary effector genes was expressed in both biotypes at a similar level. Nonetheless, we identified small sets of genes that were differentially regulated in a biotype-specific manner. Little host plant effect (universal vs. specific) was observed on the expression of candidate salivary genes. Analysis of previously-obtained genome re-sequenced data of the two biotypes revealed the copy number variations that might explain the differential expression of some candidate salivary genes. In addition, at least four candidate effector genes that were present in the alfalfa biotype but might not be encoded in the pea biotype were identified. This work sets the stage for future functional characterization of candidate genes potentially involved in the determination of plant specificity of pea aphid biotypes.